Commercial vegetable and polyculture fish production in Bangladesh: their impacts on household income and dietary quality - Bouis, Howarth E. (United Nations University, 2000)
Given the low access that women in rural Bangladesh have to productive assets, their crucial role as caretakers, and their high vulnerability to micronutrient deficiencies, numerous non-governmental organizations target women for food-based income-generating activities. Three such programmes were examined, which promote adoption of polyculture fish production (two sites) and commercial vegetable production (one site). The programmes evaluated had income generation—and not better nutrition—as their primary objective. The fish and vegetable technologies were found to be more profitable than rice production, although rice production provided a higher share of total income. On the basis of the evidence collected, there is little reason to believe that adoption of the two technologies has improved the micronutrient status of members of adopting households through better dietary quality. There was no finding of disproportionately high own-consumption of fish and vegetables by adopting households. The impacts on overall household income, although positive, were not strong. The effects of adoption on women's status and time allocation do not change this conclusion.It is consumers in general who benefit from research, extension, and credit programmes to increase the market supply of vegetables and fish. All other things being equal, increased market supply will lower prices for these foods. Although inflation-adjusted cereal prices in Bangladesh have fallen by 40% over the last 25 years (a remarkable achievement), real prices of lentils, vegetables, and animal products have increased by 25% to 50%. Real fish prices have perhaps doubled. Dietary quality for the poor may be declining over time due to these price effects.